Microwave Dielectric Properties of Hevea Rubber Latex in the Temperature Range of -30°C to 50°C - Hassan, Jumiah; Khalid, Kaida; Wan Yusof, Wan Mohamad Daud (Universiti Putra Malaysia Press, 1997)
The dielectric properties of hevea rubber latex were measured at selected microwave frequencies over the temperature range of -30°C to 50°C. The measurements were made on latex concentrate, fresh latex and diluted fresh latex by using an open-ended coaxial-line probe and an automated network analyser. There is a steep increase in the dielectric constant of about one order and dielectric loss factor of about two orders as the phase of latex changes from solid to liquid. The effect of temperature on the ionic conductivity at 0.2 GHz and dipole orientation at 2.6 GHz and above can be clearly seen in these studies. It was found that, the frequency around 10 GHz is a suitable operating frequency for microwave latexometer as dielectric properties are fairly independent of the temperature.